Comparison of supination flexion and hyperpronation technique in reduction of pulled elbow patients presenting to a tertiary health center in Western Nepal - Sigdel, Bhim; Adhikari, Shirish; Pokharel, Jhapindra; Pariyar, Bijay; Pahari, Sunil; Aryal, Niranjan (Grande Medical Journal, 2025)
Background: Pulled elbow (Nursemaid’s elbow) or radial head subluxation is a common upper extremity injury in young children and a frequent reason for visiting the Emergency Department. Supination flexion and hyperpronation are two methods described in the literature for reducing this subluxation. The purpose of this study was to identify the most effective method of reduction for pulled elbow in our setting. Method: This was an observational cross-sectional study including children below 5 years with a provisional diagnosis of pulled elbow and divided into two groups based on the type of reduction method used. The success at the first attempt of the reduction and pain perceived during the reduction using the Wong Baker Faces Pain Rating Scale score were taken as indicators of effectiveness, and age, gender, laterality, and mechanism of injury as demographic indicators were calculated. Result: Among 84 patients included in the study, the mean age of presentation was 2.92 ± 1.27 years, girls were 51.2%, left side involvement was 66.6% and pulling of the arm (80.95%) was the most common mechanism of injury. The hyperpronation mechanism was more successful than supination flexion during the first attempt reduction (88.1% vs 76.2%) but was not statistically significant (p=0.15). Pain levels perceived during reduction were also less (5.762 ± 1.1 vs 7.33 ± 1.3) in the hyperpronation group as compared to the supination flexion group, and this was statistically significant (p <0.001). Conclusion: The hyperpronation method is more effective than the supination flexion method for the reduction of pulled elbow in children in our setup.